Новый подвид ящурки песчаной — Eremias scripta pherganensis ssp. n. (Reptilia, Sauria) из Узбекистана - Щербак, Н.Н.; Вашетко, Э.В. (Вестник зоологии, 1973)
Studying of samples from populations of Eremias scripta areal substantiated the rightful distinguishment of subspecies E. scripta lasdini (T z a r., 1918) and permitted the population from Ferghana valley, the lizards of which are distinguished by the peculiarities of drawing on the back and by the folidosis characters to be made a subspecies E. scripta pherganensis ssp. n. A description of the new subspecies is given.